The neural circuits of monogamous behavior - López-Gutiérrez, María Fernanda; Mejía-Chávez, Sara; Alcauter, Sarael; Portillo, Wendy (Frontiers in Neural Circuits, 2022)
The interest in studying the neural circuits related to mating behavior and mate choice in monogamous species lies in the parallels found between human social structure and sexual behavior and that of other mammals that exhibit social monogamy (Debiec, 2007), potentially expanding our understanding of human neurobiology and its underlying mechanisms. Extensive research has suggested that social monogamy, as opposed to non-monogamy in mammals, is a consequence of the neural encoding of sociosensory information from the sexual partner with an increased reward value (Numan and Young, 2016; Walum and Young, 2018). Thus, the reinforced value of the mate outweighs the reward value of mating with any other potential sexual partners. This mechanism reinforces the social relationship of a breeding pair, commonly defined as a pair bond. In addition to accentuated prosocial behaviors towards the partner, other characteristic behaviors may appear, such as territorial and partner guarding, selective aggression towards unfamiliar conspecifics, and biparental care. Concomitantly, social buffering and distress upon partner separation are also observed (Young and Wang, 2004). The following work intends to overview and compare known neural and functional circuits that are related to mating and sexual behavior in monogamous mammals. We will particularly discuss reports on Cricetid rodents of the Microtus and Peromyscus genus, and New World primates, such as the Callicebinae subfamily of the titi monkey and the marmoset (Callithrix spp.). In addition, we will mention the main factors that modulate the neural circuits related to social monogamy and how that modulation may reflect phenotypic differences, ultimately creating the widely observed diversity in social behavior.